(untitled) (diségno, 2022)
Issue 11 of diségno aims to make the comparison between Drawing and Design grow and mature, to think about the limits and margins of two disciplines that deal with the representation of the world of objects and the other with their construction, opening up further spaces on visual communication and visual design. [read more]